2018
DOI: 10.1007/s11469-018-9961-1
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Problematic Smartphone Use among Chinese University Students: Associations with Academic Anxiety, Academic Procrastination, Self-Regulation and Subjective Wellbeing

Abstract: Over the past decade, there have been an increasing number of studies that have investigated problematic and/or 'addictive' smartphone use. The present study explored the prevalence and correlates of problematic smartphone use (PSU) among Chinese university students. Few studies have investigated relationships between PSU and factors such as academic anxiety, academic procrastination, self-regulation, and subjective wellbeing. The present study proposed and tested a hypothetical model of relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
86
0
31

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 58 publications
(80 reference statements)
11
86
0
31
Order By: Relevance
“…Other studies found that PSU damaged adolescents' psychological and social functions (Yen et al, 2009), and it led to behavioral problems, such as aggression and smoking (Augner and Hacker, 2012). Furthermore, PSU might be associated with concentration difficulties (Söderqvist et al, 2008) and poor academic performance (Hawi and Samaha, 2016;Samaha and Hawi, 2016;Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found that PSU damaged adolescents' psychological and social functions (Yen et al, 2009), and it led to behavioral problems, such as aggression and smoking (Augner and Hacker, 2012). Furthermore, PSU might be associated with concentration difficulties (Söderqvist et al, 2008) and poor academic performance (Hawi and Samaha, 2016;Samaha and Hawi, 2016;Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the causes and consequences of PSU are complicated. A number of studies in different contexts have found that PSU is associated with poor well-being and other mental health issues (Dayapoglu et al 2016;Hong et al 2012;Leung 2008;Long et al 2016;Yang et al 2019a). For example, excessive smartphone use has been found to predict anxiety (Lepp et al 2014).…”
mentioning
confidence: 99%
“…A procrastinação é uma prática comum (Yockey, 2016), definida como o ato de adiar a realização de atividades de forma deliberada ou não (Kim, Fernandez, & Terrier, 2017). Pesquisas tem se dedicado a estudar as diferentes conotações que a procrastinação pode apresentar, ora centrando-se nos aspectos funcionais (e.g., buscar por desenvolver tarefas da melhor maneira possível; Chu & Choi, 2005;Schraw, Wadkins, & Olafson, 2007), ora nos não funcionais (e.g., dificuldade de finalização de tarefas por alto grau de exigencia; Abramowski, 2018;Yang, Asbury, & Griffiths, 2018). No contexto acadêmico, sua influência se mostra mais acentuada, por exemplo, Balkis e Duru (2016) afirmam que 80-90% dos estudantes universitários adiam seus deveres acadêmicos, tornando-se um fenômeno crescente onde estudantes classificados como procrastinadores tendem a apresentar desempenho menor quando comparados a acadêmicos "não procrastinadores" (Closson & Boutilier, 2017).…”
Section: Procrastinação Acadêmicaunclassified
“…De acordo com Balkis (2013), a procrastinação acadêmica é dinâmica, relacionando-se a características pessoais, ambientais e comportamentais. Além disso, sua ocorrência tem sido relacionada a grades curriculares muito extensas, à redução do estado de bem-estar, aos altos níveis de estresse, apresentando-se como um preditor negativo da realização acadêmica e do bem-estar subjetivo (McCloskey, 2011;Steel & Klingsieck, 2016;Yang et al, 2018).…”
Section: Procrastinação Acadêmicaunclassified